Correlation of prothrombin time and activated partial thromboplastin time with serum immunoglobulin and M-band in newly diagnosed multiple myeloma patients - Shah, Javid R.; Bashir, Nusrat; Wani, Lateef A.; Bilal, Sheikh; Manzoor, Fahim; Koul, Rakesh; Yousuf, Mohammad (International Journal of Research in Medical Sciences, 2023)
Background: Multiple myeloma is the second most frequent malignancy which constitute 13% of hematologic cancers. Thrombotic and hemorrhagic complications have been frequently observed in multiple myeloma patients. Methods: The study was conducted in the department of pathology, Government medical college Srinagar. A total of fifty (50) patients were recruited for the study. The patients were advised coagulation profile and complete myeloma profile. Results: Our findings indicate that prolonged PT is associated with high serum IgG levels. A mild to moderate correlation was seen with kappa-free light chains and an inverse correlation was seen between PT and lmbda-free light chains. Conclusions: Screening of multiple myeloma for hemostatic abnormalities at the diagnosis should improve prognosis in such cases.